ANALYSIS OF THE IMPLEMENTATION OF COASTAL RECLAMATION IN TELUK PALU - Nabbilah Amir; Aldo Halim (Journal Equity of Law and Governance, 2021)
The coastal reclamation of Teluk Palu is carried out in Palu City, Central Sulawesi aims to make the coastal area a new tourism area and increase the regional income of Palu City. The land formed as a tourism area can be used by local governments to attract foreign investors to invest their capital. However, coastal reclamation in addition to providing benefits also has a negative impact on the surrounding environment and the people living around the coast. The aims of this research are to find out more about the process of implementing coastal reclamation in Teluk Palu and the impact of the implementation of coastal reclamation in Teluk Palu. The research method used is a normative juridical with an empirical juridical approach as research support. The data sources are divided into primary and secondary data.